Artes de dizer, nutrir e fazer etnomatemático em uma feira livre Arts of saying, nourishing and making ethnomathematics in a free fair - Almeida, Shirley Patrícia Nogueira de Castro e; Crisostomo, Edson (Educação Matemática Pesquisa Revista do Programa de Estudos Pós-Graduados em Educação Matemática, 2017)
Neste trabalho tivemos por objetivo identificar os saberes e fazeres dos feirantes e fregueses que fazem a feira do bairro Major Prates, em Montes Claros, região Norte de Minas Gerais. Por meio da observação das relações tecidas naquele espaço, desenvolvemos uma investigação sobre as práticas cotidianas no contexto da Feira Livre, a partir da análise das artes de dizer, de nutrir e de fazer etnomatemático. Fizemos uma análise qualitativa dos gestos e vozes dos sujeitos que fazem a feira que evidenciam uma utilização eficiente de conceitos matemáticos em sua prática comercial cotidiana. Verificamos que a Feira do Major Prates tem se consolidado por sua vocação marcadamente hortifrutigranjeira, bem como pela possibilidade de convivência familiar das pessoas que a frequentam para se nutrir, divertir-se e trabalhar. This work aims to identify the knowledges and achievements of the stallholders and customers who "make the fair" of the Major Prates neighborhood, in Montes Claros, the northern region of Minas Gerais. Through the observation of the relationships woven in that space, we developed an investigation about the daily practices in the Free Fair’s context, from the analysis of the arts of saying, nourishing and making ethnomathematics. We made a qualitative analysis of the gestures and voices of the subjects who "make the fair" that shows an efficient use of mathematical concepts in their daily commercial practice. We have verified that the Major Prates’ Fair has been consolidated by its vocation markedly “hortifrutigranjeira”, as well as by the possibility of familiar coexistence of the people who attend it to nourish, have fun and work.